Understanding COVID-19 preventive behavior among health workers in Bali’s referral hospitals: A socio-ecological approach - Putu Chrisdayanti Suada Putri; Dinar Saurmauli Lubis; Cokorda Bagus Jaya Lesmana (Public Health and Preventive Medicine Archive, 2025)
Background and purpose: Coronavirus Disease (COVID-19) is one of global health problems which affect all aspects of people’s life. Because hospitals are high-risk environments for COVID-19 transmission, healthcare workers' preventive behaviors are critical. These behaviors are shaped by the interaction of personal, interpersonal, and institutional factors. Therefore, this study aimed to explore the COVID-19 preventive behaviors of registration staff at three referral hospitals in Bali, utilizing the Socio-Ecological Model. Methods: This qualitative study applied a phenomenological approach based on the Socio-Ecological Model of Health Behavior. The study was conducted in March 2021 at three COVID-19 referral hospitals in Bali (Sanglah, Wangaya, and Tabanan Hospitals). We purposely sampled 50 health workers from the registration section. Data were collected via online semi-structured interviews, observations and documentation, then analyzed using phenomenological techniques. Data validity was ensured through source triangulation (comparing insights from staff in outpatient, emergency, and COVID-19 registration posts, as well as the unit heads) and methods triangulation. Results: The findings demonstrate that preventive behaviors at the personal level interacted dynamically with interpersonal and institutional dimensions. At personal level, workers adhered to standard protocols (masking, handwashing, and physical distancing), utilized hand sanitizer after patient registration, conducted routine disinfection, and wore appropriate personal protective equipment. Individual actions were reinforced through informational support from peers on how to safely interact with patients and their families. At the institutional level, the health facilities supported these personal and interpersonal efforts through official preventive policies and by physically modifying the environment in registration areas. Conclusion: Preventing the transmission of infectious diseases in healthcare facilities requires a comprehensive approach that encompasses individual behavior, interpersonal support, a safety-oriented work culture, and robust institutional policies. These findings may serve as a reference for developing training programs, establishing standard operating procedures (SOPs), and strengthening a culture of safety among healthcare workers, thereby enhancing their preparedness to respond to future infectious disease outbreaks.